The Effect of Green Accounting Implementation, Material Flow Cost Accounting, Enviromental Perfomance, and Enviromental Disclosure on Sustainable Development Goals (SDGs) - Kurniawan, Relin; Fitranita, Vika (Jurnal Akuntansi, Manajemen dan Ekonomi, 2024)
The rapid development of the industrial world has led to competition between companies to achieve their goals. The environment around the company also has an impact as a result of this competition. The purpose of this study was to examine the effect of Green Accounting, Material Flow Cost Accounting (MFCA), Enviromental Performance, and Enviromental Disclosure on Sustainable Development Goals (SDGs). The population used is oil and gas sector companies listed on the Indonesia Stock Exchange (IDX) in 2018 - 2022. The sample technique used Purposive Sampling, so that the sample amounted to 40 (8 companies for 5 years). The results showed that Green Accounting and Environmental Performance were able to improve SDGs, while Material Flow Cost Accounting (MFCA) and Environmental Disclosure had no influence on SDGs. This study provides implications for oil and gas sector companies that implement Green Accounting and disclose Enviromental Performance by incurring environmental costs will help improve the achievement of SDGs.